2019
DOI: 10.1093/jme/tjz231
|View full text |Cite
|
Sign up to set email alerts
|

Epidemic West Nile Virus Infection Rates and Endemic Population Dynamics Among South Dakota Mosquitoes: A 15-yr Study from the United States Northern Great Plains

Abstract: Mosquito surveillance has been conducted across South Dakota (SD) to record and track potential West Nile virus (WNV) vectors since 2004. During this time, communities from 29 counties collected nearly 5.5 million mosquitoes, providing data from over 60,000 unique trapping nights. The nuisance mosquito, Aedes vexans (Meigen) was the most abundant species in the state (39.9%), and most abundant in most regions. The WNV vector, Culex tarsalis Coquillett (Diptera: Culicidae), was the second most abundant species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…However, high mosquito abundances and frequent bites do not necessarily translate into high risk of WNV transmission. In South Dakota, the most important nuisance mosquito is Aedes vexans , which occurs in large numbers in spring and early summer after heavy rains flood their breeding habitats ( Vincent et al. 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, high mosquito abundances and frequent bites do not necessarily translate into high risk of WNV transmission. In South Dakota, the most important nuisance mosquito is Aedes vexans , which occurs in large numbers in spring and early summer after heavy rains flood their breeding habitats ( Vincent et al. 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…We chose this approach because it was relatively insensitive to changes in the numbers and locations of mosquito traps from year to year, allowing us to use all of our statewide mosquito data for model calibration and prediction. A prior study found that, in South Dakota, mosquito abundance is not a strong indicator of human WNV risk ( Vincent et al. 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 This assay has been used in the detection or surveillance of WNV in people, mosquitoes, birds, or horses. 14,30,34 To meet the need for simultaneous testing of multiple pathogens, we modified the assay protocol and validated the assay, which showed excellent sensitivity and specificity. A study using the primers/probe set detected as few as 10 The same primers/probe set also showed high sensitivity in our study, with a detection limit of 10 copies per reaction, and the sensitivity was not affected by the vector background.…”
Section: Discussionmentioning
confidence: 99%
“…1 This assay has been used in the detection or surveillance of WNV in people, mosquitoes, birds, or horses. 14,30,34 To meet the need for simultaneous testing of multiple pathogens, we modified the assay protocol and validated the assay, which showed excellent sensitivity and specificity. A study using the primers/probe set detected as few as 10 1.7–2.3 pfu of WNV/mL in infected mosquitoes, C. pipiens quinquefasciatus.…”
Section: Discussionmentioning
confidence: 99%